PERFORMANCE OF REINFORCED CONCRETE STRUCTURE â DUAL SYSTEM WITH SEISMIC PROTECTION SYSTEM VISCOELASTIC DAMPER âINVERTED Vâ - Saputra Gunawan, Andri
Most of reinforced concrete structure design which is able to overcome strong earthquake is based on strong column – weak beam principle. In this system, structural element damage caused by strong earthquake cannot be avoided. The damage of structural element can disipate input energy through yielding so the structure is still functional. Element structural damage can be avoided by seismic protection system installation. The system is behave as a earthquake energy dissipator so the damage is reduced. In this study, the peformance of reinforced concrete structure with dual system will be compared to reinforced concrete structure with dual system and seismic protection system. The system is viscoelastic damper with Inverted V configuration. The performance comparison includes strucutral dynamic characters, base shear, structure response, damage of structural element, viscoelastic damper’s force contribution, input energy, and strucure response energy. This study will use Direct Integration Non Linear Time History and Modal Linear Time History. Based on parameter comparison of structure performance, it shows that fundamental period of structure is decreased along with increased strength properties of viscoelastic materials, but it doesn’t change modal mass participation ration. Base shear force that is received by structure doesn’t change significantly. Structure response is decreased along with increased strength properties of viscoelastic materials. Damage of strucutural element is also decreased. Viscoelastic dampers can work optimaly when the damper able to compensate the rigidity of structure. Structure response energy remains constant along with increased strength properties of viscoelastic materials. However, it is compensated with decreased maximum input energy, maximum potential energy, and maximum kinetic energy. Overall, the reinforced concrete structure with viscoelastic damper installation has better performance to overcome the strong earthquake.